Climatic Media : Transpacific Experiments in Atmospheric Control - Furuhata, Yuriko, 1973- (Book collections on Project MUSE., 2022)
"In Climatic Media, Yuriko Furuhata traces climate engineering from the early twentieth century to the present, emphasizing the legacies of Japan's empire-building and its Cold War alliance with the United States. Furuhata boldly expands the scope of media studies to consider technologies that chemically "condition" the Earth's atmosphere and socially "condition" the conduct of people, focusing on the attempts to monitor and modify indoor and outdoor atmospheres by Japanese scientists, technicians, architects, and artists in conjunction with their American counterparts. She charts the geopolitical contexts of what she calls climatic media by examining a range of technologies such as cloud seeding and artificial snowflakes, digital computing used for weather forecasting and weather control, cybernetics for urban planning and policing, Nakaya Fujiko's fog sculpture, and the architectural experiments of Tange Lab and the Metabolists, who sought to design climate-controlled capsule housing and domed cities. Furuhata's transpacific analysis offers a novel take on the elemental conditions of media and climate change"--